Intramuscular lipid oxidation and obesity - Houmard, Joseph A. (East Carolina University, 2008)
There is an accumulating amount of evidence indicating that lipid oxidation is depressed in the skeletal muscle of obese individuals. Decrements in fatty acid oxidation (FAO) have been reported with obesity in models ranging from whole body measurements to isolated skeletal muscle preparations as well as in myotubes raised in culture. This reduction appears to be associated with a depression in the activities of enzymes involved in various steps of lipid oxidation, which subsequently partitions lipid entering the cell toward storage. The defect in FAO in skeletal muscle may be critical in relation to health, as a reduction in the capacity for lipid oxidation could directly or indirectly contribute to the insulin resistance commonly evident with obesity. Although less characterized, a decrement in FAO has also been linked with weight gain, which suggests that this characteristic may be an integral aspect leading to the obese state. In terms of intervention, weight loss does not seem to correct the defect in FAO with obesity. This review will provide evidence supporting a reduction in muscle FAO with obesity. Originally published AJP - Regulatory, Integrative and Comparative Physiology 294(4) 2009.
Keywords: Skeletal muscle; Metabolism; Insulin action